Para além de uma oposição: o papel da escola na construção da pessoa na tekoá Nhamandu Mirim - Bossada, Pedro Luiz Alves (Universidade Federal de São Carlos, 2026)
In this dissertation, we present an ethnography of the Tupi Guarani school in the tekoá Nhamandu Mirim, located in the Piaçaguera Indigenous Land (coastal region of the state of São Paulo). We follow the school as a situated social practice, a place of composition and passage where regimes of knowledge, temporalities, bodily practices, and languages are brought into relation and are continuously (re)produced by teachers, students, and the community at large. In our analysis, we seek to move beyond the opposition between “Indigenous education” and “Indigenous school education,” which is common in the literature on the topic, showing that the school does not replace other spaces of formation, but has come to occupy a recently prominent place in person-making. From this perspective, we foreground the notion of djagwatá (“collective walking”) as an analytical key for thinking about how knowledge is set in motion in Nhamandu Mirim, treating error as a constitutive element of a formative and ethical regime. Finally, we examine strategies for indigenizing the school, paying special attention to the revitalization of Guarani Nhandewa and to the incorporation of Djatsyá as a cosmological principle for organizing school time. We aim to show that this indigenization emerges from lutas (“struggles”) and conquistas (“achievements”) while also raising challenges for the future.
Beyond an opposition: the school's role in the construction of the person in the tekoá Nhamandu Mirim
Keywords: Tupi Guarani; Escola indígena; Construção da pessoa; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA; 4. Educação de Qualidade